Nurse-led care clinics: transformative healthcare model or modern branding buzzword? A critical systematic review - Suganthi, S.; A., Kalaiselvi Xavier; Munusamy, Gomathi; Vanaja, P.; Londhe, Snehal Rajendra; Ahmad, Meraj; Muthukumaran, Anjalatchi; Prabha, N.; Priya, J. Sathya Shenbega; P. F., Regina; Umar, Mohammed (International Journal of Research in Medical Sciences, 2026)
Healthcare systems worldwide are increasingly challenged by rising chronic disease burdens, workforce shortages, escalating healthcare costs, and growing demands for accessible, high-quality care. In response, nurse-led care clinics (NLCCs) have emerged as innovative healthcare delivery models designed to enhance service accessibility, continuity of care, and patient outcomes. This critical review examines whether NLCCs represent a transformative healthcare model or primarily function as a contemporary healthcare branding strategy. A comprehensive review of published literature was conducted using evidence from primary care, chronic disease management, cardiovascular services, oncology, mental health, community healthcare, and advanced nursing practice settings. The findings indicate that nurse-led clinics consistently achieve clinical outcomes comparable to physician-led services while demonstrating high levels of patient satisfaction, improved self-management, enhanced continuity of care, and increased healthcare accessibility, particularly among underserved populations. Evidence also suggests potential economic benefits through reduced hospital admissions, lower emergency department utilization, and improved chronic disease management. However, significant variability exists in clinic structures, scope of practice, regulatory frameworks, and operational definitions, limiting direct comparisons across studies. Furthermore, some claims regarding the transformative impact of nurse-led care may exceed the strength of available evidence, highlighting the need for standardized evaluation frameworks. Overall, the review concludes that NLCCs are more than a healthcare branding phenomenon and possess substantial potential to improve healthcare quality, equity, and sustainability when supported by appropriate policy, education, and organizational infrastructures. Future research should focus on long-term outcomes, cost-effectiveness, and implementation strategies across diverse healthcare systems.